Post-COVID syndrome patients show reduced anti-Spike antibodies compared to COVID-recovered controls, but enhanced IgG4/IgG1 switch after the third vaccine dose - Rossi, Nineth; Benítez-Cruz, Javier; Marín-García, Patricia; Azcárate, Isabel G.; González-Escalada, Alba; Hervás, Oscar G.; Alarcón, Balbino; Regueiro, José R.; Bautista, José M.; Martinez-Quiles, Narcisa (Frontiers in Immunology, 2025)
IntroductionLong COVID and post-COVID syndromes represent a significant global health crisis and a substantial societal challenge. Although an altered immunological response has been suggested as a possible underlying mechanism, the antibody response to vaccination and infection of the patients remains unclear.MethodsWe studied a post-COVID syndrome cohort compared to a COVID-recovered cohort. Initially, we established the risk factors and the evolution of symptoms. Then, we analyzed the antibody response, focusing on immunoglobulin subclasses. Apart from determining immunoglobulin G (IgG) against the Nucleocapsid, which is a marker of infection, we analyzed IgG and its subclasses against the full-length Spike, and against the receptor-binding domain (RBD). Additionally, we examined the switch to IgG4, which can be promoted by repeated antigen exposure.ResultsWe show the major risk factors for developing post-COVID syndrome, such as infection before vaccination and comorbidities. Furthermore, we describe the evolution of the post-COVID symptoms, which agrees with previous reports. Regarding the antibody response, we found that compared to COVID-recovered individuals, post-COVID patients present readily detectable anti-Nucleocapsid IgG but low quantities of anti-Spike antibodies. Nevertheless, the anti-RBD IgG1 levels are similar between post-COVID and COVID samples. Interestingly, post-COVID patients with three vaccine doses, who were infected before vaccination by the Wuhan strain and subsequently reinfected post-Omicron, show decreased Spike response but intensified anti-RBD IgG4/IgG1 switch, compared to their non-reinfected post-COVID counterparts.DiscussionOur results support a differential antibody response in post-COVID versus COVID-recovered patients, which might be relevant for post-COVID syndrome treatment, including appropriate recall vaccination strategies for the still-circulating SARS-CoV-2.